2022
DOI: 10.1186/s12873-022-00688-4
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective descriptive analysis of non-physician-performed prehospital endotracheal intubation practices and performance in South Africa

Abstract: Introduction Prehospital advanced airway management, including endotracheal intubation (ETI), is one of the most commonly performed advanced life support skills. In South Africa, prehospital ETI is performed by non-physician prehospital providers. This practice has recently come under scrutiny due to lower first pass (FPS) and overall success rates, a high incidence of adverse events (AEs), and limited evidence regarding the impact of ETI on mortality. The aim of this study was to describe non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The demographic descriptors of the patients were similar to other studies done in the South African pre-hospital setting with the predominant population being young males with trauma [ 17 , [20] , [21] , [22] ]. Interestingly, males were more likely to receive PISA than females.…”
Section: Discussionsupporting
confidence: 70%
“…The demographic descriptors of the patients were similar to other studies done in the South African pre-hospital setting with the predominant population being young males with trauma [ 17 , [20] , [21] , [22] ]. Interestingly, males were more likely to receive PISA than females.…”
Section: Discussionsupporting
confidence: 70%
“…86,[96][97][98] Advanced transport systems like HEMS and Urgent Medical Aid Service (SAMU) have reduced transportation time and played a crucial role in reducing mortality. 80,99,100 A study conducted by Sobuwa, et al 101 showed that prehospital intubations performed among traumatic brain injury patients did not demonstrate improved outcomes, however, another study conducted in South Africa reported a 98% success rate of prehospital endotracheal intubation 102 (Table 4 80,81,86,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] ).…”
Section: Status Of Prehospital Emergency Care Servicesmentioning
confidence: 99%
“…Thus, modern healthcare scientists suggest studying various issues using the descriptive analysis method. For example, Riediger N. D. et al [58] used descriptive analysis of food pantries in twelve American states; Taljaard L. et al [59] conducted a descriptive analysis of the case mix in East London, South Africa; Bayou N. B. et al [60] used a descriptive structural analysis of quality of labor and delivery care in Ethiopia; and Wylie C. A. et al [61] described a retrospective descriptive analysis. Descriptive analysis is also very often used in social sciences (18.56%).…”
Section: Introductionmentioning
confidence: 99%
“…61); and the highest comprehensive integral indicators were found in Norway (0.61) and Sweden (0.60). These values indicate the best state of indicators that determine the level of the health system development in the countries.…”
mentioning
confidence: 96%